Slags as agricultural limes : reactivity and heavy metal and phosphorus bio-availability - Claassens, A.S. (Andries Stephanus), 1943- (University of Pretoria, 2013)
Dissertation (MSc (Soil Science))--University of Pretoria, 2007.